Influence of Cancer News on Quality of Life of Patients Families: An Observational Study - Muhammad Tariq, Sehrish Sarwar Baloch, Saqib Raza Khan, Mehwish Shahzadi, Mohammad Daanyaal Khan, Muhammad Jawad Zahid, Samad Jehangir Shah, Yasmin Abdul Rashid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Malignant disease diagnosis brings great psychological suffering to the patient, and the sickness might have catastrophic ramifications for the relatives. Objective: To assess influence of cancer news on quality of life of patient’s families Methodology: This study was prospective cohort study conducted at the oncology department of tertiary care Hospitals of Peshawar for duration of one year. The quality of life was assessed as per pre defined questionnaire both from two first degree relatives at each clinical visit during treatment every week and every month for six months after completion of treatment. Data analysis was done by employing SPSS version 21. Results: A total of 180 family members were included. In the current study, the quality of life of family members was 1.54±0.57 in view of usual activities (p=0.001). Anxiety/depression score of the family members was 1.67±0.64 while in control group it was 1.50±0.64 (p=0.031). The EQ VAS score in control group was 66.5±16.7 whereas in caregivers group, it was 71.3±18.8 (P=0.023). Based on mental health, stress was observed in 98 (54.44%) participants in caregivers group. Moderate-severe depression was observed in 45 (25%) participants in caregiveres group whereas in contorl group moderate to severe depression was observed in 21 (11.67%) subjects. (p=0.041) Conclusion: Our findings reveal that family caregivers of cancer patients face mental health issues and a decline in health-related quality of life. To reduce the effect of caring on the mental health and health related quality of life of family caregivers in Pakistan, culturally suitable caregiver support programs are required.